Proteolytic Studies in Liver Homogenate in Presence of Substituted Aryl Hydrazones - Raghav, N.; Singh, Mamta; Kaur, Ravinder; Suman; Priyanka (Asian Journal of Chemistry, 2010)
Hydrazones of different arylaldehydes were synthesized and their effect on endogenous proteolysis in liver was studied. It was observed that different functional groups on the benzene moiety altered the enzymatic activity and para-nitrobenzaldehyde hydrazone exhibited maximum inhibitory effect.